The Effect of Sugar Addition and Time of Storage on Physical Quality of Fermented Milk - Ice Gianti; Herly Evanuarini (Faculty of Animal Science Universitas Brawijaya, 2011)
Fermented milkÂ is one of processing milk used one or more microorganism. The objectives of the research were to find out the effect of sugar addition and time of storage on physical quality of fermented milk. This research was using factorial Randomized Block Design. The combination of sugar addition 20% and time of storage for 4 days produced fermented milk which gave the standard of Indonesian Industry Fermented milk. It had the following properties: pH (3.8), acidity (0.85) and viscositiy (150 cps) Key words : sugar, time of storage, fermented milk